2005
DOI: 10.1038/sj.emboj.7600815
|View full text |Cite
|
Sign up to set email alerts
|

Kid cleaves specific mRNAs at UUACU sites to rescue the copy number of plasmid R1

Abstract: Stability and copy number of extra‐chromosomal elements are tightly regulated in prokaryotes and eukaryotes. Toxin Kid and antitoxin Kis are the components of the parD stability system of prokaryotic plasmid R1 and they can also function in eukaryotes. In bacteria, Kid was thought to become active only in cells that lose plasmid R1 and to cleave exclusively host mRNAs at UA(A/C/U) trinucleotide sites to eliminate plasmid‐free cells. Instead, we demonstrate here that Kid becomes active in plasmid‐containing cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…Doc Expression Leads to mRNA Stabilization. Some TA toxins lead to translation arrest indirectly by elimination of virtually all of the intracellular mRNA through their sequence-specific endoribonuclease activity [e.g., E. coli MazF (27) and ChpBK (28), Kid on plasmid R1 (29), and PemK on plasmid R100 (30)]. We analyzed the effect of Doc expression on the steady-state levels of mRNA in vivo.…”
Section: Phd Can Rescue Doc-mediated In Vitro Translation Arrest and mentioning
confidence: 99%
“…Doc Expression Leads to mRNA Stabilization. Some TA toxins lead to translation arrest indirectly by elimination of virtually all of the intracellular mRNA through their sequence-specific endoribonuclease activity [e.g., E. coli MazF (27) and ChpBK (28), Kid on plasmid R1 (29), and PemK on plasmid R100 (30)]. We analyzed the effect of Doc expression on the steady-state levels of mRNA in vivo.…”
Section: Phd Can Rescue Doc-mediated In Vitro Translation Arrest and mentioning
confidence: 99%
“…We also found that Kid cleaved mRNA at UUACU sites, which appeared well suited to trigger a response that prevented plasmid loss and increased R1 CNs without killing cells, as suggested by our results. In view of all this, we argued that Kid and Kis functioned as a rescue system for plasmid R1, and not as a PSK system (24). This proposal cannot be supported by results elsewhere, suggesting that Kid may cleave mRNA at simpler UAH sites (with H being A, C, or U) (25,26), a view that has prevailed in the literature (14,16,(27)(28)(29).…”
Section: Significancementioning
confidence: 38%
“…Thus, overexpression of copA, an antisense RNA that impedes translation of repA, reduces R1 content in host cells as they divide and leads to the eventual production of plasmid-free descendants in the population (33). Two observations made when we used this strategy in E. coli cells carrying an R1 derivative bearing kis-kid argued against a PSK function for this TA pair (24). First, activation of Kid occurred in cells that still contained the plasmid; second, this inhibited growth of our cultures but did not kill cells, because they resumed proliferation when further expression of copA was discontinued.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, DTR-mediated cell-ablation methods are currently limited to rodents and it is unclear if they work with developing embryos. A third controllable, cell death technology is the endoribonuclease Kid toxin (de la Cueva-Mendez et al, 2003;Pimentel et al, 2005; Fig. 2K-M, Supplementary Movie S3).…”
Section: M2(h37a) Targeted Cellablation Versus Other Toxic Protein Symentioning
confidence: 99%